Creating engaging science projects with netsblox - Broll, Brian; Zare, Hamid; Ledeczi, Akos (2017 IEEE Blocks and Beyond Workshop (B&B), 2017)
NetsBlox is a visual blocks-based programming language that supports distributed programming. NetsBlox includes Remote Procedure Calls (RPC) that provide access to a set of online scientific data sources such as maps, weather, earthquakes, astronomy imagery, air pollution, etc. This demonstration shows how to use these RPCs to create engaging science projects.